Journeys of adjustment: the experiences of adolescents living with juvenile idiopathic arthritis. (6th October 2014) - Cartwright, T.; Fraser, E.; Edmunds, S.; Wilkinson, N.; Jacobs, K.
Abstract Background Juvenile idiopathic arthritis (JIA) is one of the most common diseases of childhood causing pain, swelling of joints and reduced mobility. Previous research has focused on the challenges and psychosocial impact of JIA, but there has been limited attention given to how young people adjust and adapt to living with a long‐term condition such as JIA. The aim of this qualitative study was therefore to explore adolescents' experiences of living with JIA, with particular focus on the process of adjustment. Methods Ten adolescents (7 female, 3 male) aged 13–17 years with good treatment adherence were recruited from an adolescent arthritis clinic. In‐depth interviews were conducted, and data were analysed by two researchers independently using interpretative phenomenological analysis. Results These adolescents described the physical and psychosocial 'burden of living with JIA' and the challenges faced by an underlying preoccupation 'to be a normal teenager'. However, their accounts also revealed ways in which they regained agency and developed 'resilience through taking control' over their lives. This resilience helped the adolescents re‐establish a sense of well‐being through an ongoing process of 'acceptance and self‐growth'. Conclusions Although much research has adopted a deficit model that focuses on adjustment problems, the current study highlights the resourcefulness of young people in managing the challenges of living with a long‐term condition. These experiences of successful adjustment can be used as the basis of positive, strength‐based intervention approaches for adolescents with arthritis to enhance resilience and well‐being.